Transmembrane Collagens in Neuromuscular Development and Disorders - Wakabayashi, Tomoko (Frontiers in Molecular Neuroscience, 2021)
Neuromuscular development is a multistep process that involves interactions among various extracellular and transmembrane molecules that facilitate the precise targeting of motor axons to synaptogenic regions of the target muscle. Collagenous proteins with transmembrane domains have recently emerged as molecules that play essential roles in multiple aspects of neuromuscular formation. Membrane-associated collagens with interrupted triple helices (MACITs) are classified as an unconventional subtype of the collagen superfamily and have been implicated in cell adhesion in a variety of tissues, including the neuromuscular system. Collagen XXV, the latest member of the MACITs, plays an essential role in motor axon growth within the developing muscle. In humans, loss-of-function mutations of collagen XXV result in developmental ocular motor disorders. In contrast, collagen XIII contributes to the formation and maintenance of neuromuscular junctions (NMJs), and disruption of its function leads to congenital myasthenic syndrome. Transmembrane collagens are conserved not only in mammals but also in organisms such as C. elegans, where a single MACIT, COL-99, has been documented to function in motor innervation. Furthermore, in C. elegans, a collagen-like transmembrane protein, UNC-122, is implicated in the structural and functional integrity of the NMJ. This review summarizes recent advances in understanding the roles of transmembrane collagens and underlying molecular mechanisms in multiple aspects of neuromuscular development and disorders.